The Irony of Rorty's Lack of Theological Irony - Grant, Colin (Toronto journal of theology, 2006)
The subtlety that characterizes Richard Rorty's pragmatic postmodernism eludes him when it come to matters theological. There he clearly demonstrates precisely what his writings are meant to expose and discard—realism, representation and foundationalism. He has no doubt about the unreality of God; he presents this knowledge as a direct representation of the way things are; and he does so in a way that makes this atheistic vision foundational for his whole approach. This is directly contrary to the tentativeness that should characterize ironists, who, by definition, are "always aware of the contingency and fragility of their final vocabulary." This raises questions about why Rorty does not deal with theology with irony, rather than in the absolutist and dogmatic terms he does use; it also suggests that Rorty himself, and perhaps postmoderns generally, are not as superior to reality, representation and foundations as they would have us think, including theological realism, representation and foundations.